P475 Infections and malignancies during anti-TNF therapy in IBD patients affect all age groups – results from a 13-yr real-world retrospective study. (30th January 2023) - Majumder, S; Melanie, L; Joanne, D; Naveen, S; Quraishi, M N; Cooney, R; Ghosh, S; Iacucci, M; N Shivaji, U
Abstract: Background: Anti-TNFα is the first class of biologics approved for treatment of moderate-to-severely active Inflammatory Bowel Disease (IBD). More than two decades on, anti-TNFs remain one of the most commonly used biologics for both Ulcerative Colitis (UC) and Crohn's Disease (CD), and often as first-line therapy. Although effective, they cause several adverse events (AEs), sometimes requiring withdrawal of therapy. We aimed to report on AEs with a focus on risk of infections and malignancies in this large cohort. Methods: All IBD patients exposed to anti-TNF therapy were identified from EMR at two centres of a large tertiary referral centre between January 2009 and June 2022. All relevant demographic and clinical data were collected for those patients with well recorded AEs and follow-up. Data on cumulative AEs directly attributed to anti-TNFs that ranged from mild reactions to serious AEs (defined as those requiring review/withdrawal of anti-TNF), were collected. The data were analysed and statistical analysis carried out using the IBM® SPSS® Statistics software package Version: 28.0.0.0. Results: Total of 844 patients (M=408, 48%; median age 37years) were included, of which 61% were Caucasian. Majority had CD (608;72%) with mean age at diagnosis of 27y (SD 15y) and a median disease duration of 12years. About 50% of patients were on monotherapy and adalimumab was most frequently used (52%).There were 392 cumulative AEs recorded in this cohort with 78 infections (20% of all AEs). Among these, majority were bacterial infections, followed by Clostridium difficile . Tuberculosis(TB) was diagnosed in 5 patients. Infections were distributed evenly across all age groups with no significant difference between monotherapy or combination therapy. Majority of infections responded to anti-microbials and patients were able to resume anti-TNFs without major complications. One death recorded due to viral hepatitis. Detailed breakdown is given in Table 1. Malignancies were recorded in 16 (2%) patients and 6 were on combination therapy. Skin cancers were most common and there were no lymphomas noted. The details of malignancy are given in Table 1. Conclusion: In this large cohort, infections were one of the commonest AEs recorded during exposure to anti-TNF therapy.Bacterial infections were most frequent across all age groups requiring pause of anti-TNF in most cases and withdrawal in very few. Opportunistic infections were few and reported TB cases was as low as 0.5% of total cohort. Skin cancer was the most common malignancy and no lymphomas were reported in this cohort. Clinicians need to be aware of these risks in younger patients as anti-TNFs result in infections and malignancies across all age groups and not particularly limited to the elderly.